The Students’ Perception in Implementing Blended Learning Model on Reading Comprehension at Ninth Grade of Junior High School 6 Jambi City - Berliana Safitri; Suyadi Suyadi; Nurul Fitri (Universitas Batanghari Jambi, 2022)
This study aims was to determine students' perceptions in implementing blended learning model on reading comprehension in class IX students of SMP Negeri 6, Jambi City. The pandemic situation forced schools to issue new rules in the implementing of learning model in the classroom using blended learning model. This also changes perception of students in the learning carried out by the teacher in the classroom to help the process of students' thinking skills in reading comprehension a text or edulogy application. The research methodology in this study is a qualitative research design whose analysis requires in-depth observation. The subjects in this research were students of class IX A SMPN 6 Jambi City, using purposive sampling, which collected six students as participants, consisting of grades 1-6 and ages 14–15 years. This research gave 7 interviews in class. The results showed that IX students of SMP Negeri 6 Jambi City had difficulty comprehension English in the implementing of the blended learning model, but students also became more independent, disciplined, responsible, and diligent during the implementing of this blended learning model. because of the short learning time. The implementing of the blended learning model is carried out if the teacher wants to teach the material face-to-face and online alternately or using shifts during the learning process.